Study of number of children preferred and knowledge, attitude, practice regarding birth spacing and contraception among primigravida in urban setting - Vailaya, C. G. Raghavendra; Vailaya, C. R. Shubha (International Journal of Contemporary Pediatrics, 2020)
Background: Overpopulation is a major problem in 21st century India. 2012 census shows birth rate of 20.97/1000 people and death rate of 7.48/1000 people. Fertility rate in 2019 was 2.28 children per women. Many states implemented 2 child norms. Purpose of study is to understand the number of children preferred. Methods: A Cross sectional study was done amongst 200 primigravida women who attended antenatal clinic at SMC, Shimoga. A predesigned and pretested standard Questionnaire was used to know the number of children preferred, KAP about birth spacing, contraceptive use and unsafe abortions using objective questions. Results: Most women preferred 2 child norms across most subclasses. Most Muslims (85.7%) preferred ≥3 children. Though 100% were aware of family planning, only 46% chose to space their next pregnancy. 56.5% were in support of 2-child norm. Family pressure plays crucial role in 83.5% cases and 65.5% still opted sterilization as the first choice for contraception. Conclusions: India with high population density is staring at demographic disaster due to limited life resources. Right attitude towards birth spacing, contraceptive use, avoidance unwanted pregnancies and unsafe abortions is needed. Better female literacy, societal awareness and good medical facility at last mile is crucial. Male partner’s involvement in every step is vital.